Estudo de caso: retrofit de quadros elétricos com adequação à NR-10 de uma indústria de galvanização - SILVA, Isadora Barros (2025)
In this work, the internship report is presented, developed during the period from 06/17/2024 to 07/30/2024, during the execution of the supervised internship, under the supervision of Eng.o. Allan Silva Junior. This work was prepared following resolution no1/2024 of the Faculty of Electrical Engineering - CAMTUC, which regulates the terms of the flexibility of the Course Conclusion Work in IN no5/2023 of PROEG-UFPA. The project consisted of planning and monitoring the adequacy of 36 electrical panels in an industrial galvanization plant to ensure compliance with NR-10 safety standards. The panels were categorized into control, distribution, and socket panels. The applied methodology began with the creation of a checklist to evaluate the compliance rate with NR-10. Subsequently, adequacy activities were planned and monitored in the field. The process also involved the development of load panels and single-line diagrams. Finally, a final report was prepared, documenting the achieved compliance rate and the delivery of the adapted panels.